Hong Kong soft power : art practices in the special administrative region, 2005-2014 - Vigneron, Frank (The Chinese University Press, 2018)
In late 2014, the pro-democracy demonstrations that were called the "Umbrella Movement" revealed to the world that Hong Kong was not the money-obsessed society it had often been portrayed as. Hong Kong Soft Power is a description of the complex relationship the artists and activists of this city have had with the country it has been part of since 1997. Trying to understand all the varied forms of art practices possible in the Special Administrative Region by locating them within a relational model, and situating them within the dynamic and changing art ecosystem that has developed over the last decade, Hong Kong Soft Power describes the local art field as a site of struggle where the connections with Chinese Mainland institutions and art practices play a fundamental role. This is not to say that this influence has entirely dominated the local art field, and this book also emphasizes how the artists of the city have engaged in practices ranging from the most personal to the most socially-oriented. Analyzing the works of nearly fifty local art practitioners and a representative range of art institutions, Hong Kong Soft Power is the portrait of a culture going through the trials and tribulations of rapid political and economic changes in both its negative and positive effects